Komunikasi Dakwah Kultural di Era Digital - Ashari, M. Fahmi; Dova, Muhammad Khalil; Jaya, Canra Krisna (Journal of Da'wah, 2024)
This research aims to analyse cultural da'wah communication in the digital era. It is important for the author because in the midst of the development of the times, there has been a paradigm shift in life, including da'wah. Preaching using cultural approaches in the digital era is very important because in addition to maintaining the existence of that culture, it is also a way of preaching that is still relevant to the socio-cultural conditions of the existing society. This research uses qualitative research with data sources obtained through interviews, observation, and documentation. The result of this research is that religion and culture are two aspects that cannot be separated, even though religion and culture have certain limits, namely as long as culture does not conflict with the values of Islamic teachings. The implementation of cultural da'wah in the digital era is realised with digital platforms, namely social media, websites, and mobile applications. This is proof that Islam will always be relevant to the times and time. This means that Islamic da'wah methods will always develop and the values of Islamic teachings will always be relevant to the conditions of the times. The challenges faced in cultural da'wah in the digital era include shifting Islamic cultural values in the digitalisation era, moral decadence in social life, individualistic and materialistic lifestyles. While the opportunities obtained are that they can attract a lot of public attention, allow religious messages to be delivered in a more creative and interesting way, and can become an inseparable part of life